Membangun Bisnis dengan Menggunakan Media Sosial : Studi Kasus Akun TikTok Hijabsyifa.id - M. Yarham (Pusat Riset dan Inovasi Nasional, 2025)
Nowadays, a lot of business people are experiencing a decline in business income. This makes business people look for a way out to keep earning revenue. One of the efforts that can be done is to promote their products through social media. Currently, the popular social media platform is TikTok. The total downloads of the TikTok application in 2023 were 113 million times and Indonesia became the second country in the world to download the application the most by 11% of the total TikTok application downloads. Based on these facts, the TikTok application has the opportunity to become an effective business media in marketing its products. One of the TikTok accounts that builds its business is Hijabsyifa.id. The Hijabsyifa.id account promotes its business with a unique method, namely story telling with trending music nuances, so that it is expected to attract consumer buying interest.The purpose of this study is to determine what factors make TikTok an effective business building media in the 4.0 era. Researchers draw the conclusion that TikTok is an effective business media because TikTok has many users, is easy to use, popular with millennials, is often used by celebrities and has a TikTok ads feature that can optimize content distribution.